Tote luxe / Hariz Safuan Mohd Elmy Syamsury - Mohd Elmy Syamsury, Hariz Safuan (Universiti Teknologi MARA, Kedah, 2025)
Byzatitahir is a bag shop that is handmade using high-quality material and a cosy range of colors. It was established in October 2023. The nude-coloured tote bag is designed to be a versatile and stylish accessory. suitable for various occasions from casual outings to professional settings. However, its minimalist design emphasises functionality and elegance, making it a staple in any wardrobe. It 's also suitable for students to carry their school stuff. High-quality, durable canvas in a nude shade serves as the material of choice. The canvas has a slightly textured finish lo add a tactile dimension to the bag.As we can see by the research that I did , this brand is lacking some fun in every design and advertising aspect. Hence. I'm planning to redesign the logo to give it personality and a fun-looking concept. I'm also going to create and design the packaging so that it looks more exclusive and elegant by using an attractive nude brown colour and typeface. Thus, the name of "Tote Luxe" is from the French word "Luxe," which means luxueuse (feminine) and luxueux (masculine) to represent unisex. In other words, men and women can use this tote bag for various occasions. Furthermore, we handcraft this tote bag specifically for those who appreciate minimalist design and colour. To end the words, this nude colour tote bag is the perfect blend of style and practicality, designed to meet the needs of modern users who value both aesthetics and functionality.